Comprehensive snapshots of natural killer cells functions, signaling, molecular mechanisms and clinical utilization - Sumei Chen; Haitao Zhu; Youssef Jounaidi (Signal Transduction and Targeted Therapy)
Abstract Natural killer (NK) cells, initially identified for their rapid virus-infected and leukemia cell killing and tumor destruction, are pivotal in immunity. They exhibit multifaceted roles in cancer, viral infections, autoimmunity, pregnancy, wound healing, and more. Derived from a common lymphoid progenitor, they lack CD3, B-cell, or T-cell receptors but wield high cytotoxicity via perforin and granzymes. NK cells orchestrate immune responses, secreting inflammatory IFNγ or immunosuppressive TGFβ and IL-10. CD56dim and CD56bright NK cells execute cytotoxicity, while CD56bright cells also regulate immunity. However, beyond the CD56 dichotomy, detailed phenotypic diversity reveals many functional subsets that may not be optimal for cancer immunotherapy. In this review, we provide comprehensive and detailed snapshots of NK cells’ functions and states of activation and inhibitions in cancer, autoimmunity, angiogenesis, wound healing, pregnancy and fertility, aging, and senescence mediated by complex signaling and ligand-receptor interactions, including the impact of the environment. As the use of engineered NK cells for cancer immunotherapy accelerates, often in the footsteps of T-cell-derived engineering, we examine the interactions of NK cells with other immune effectors and relevant signaling and the limitations in the tumor microenvironment, intending to understand how to enhance their cytolytic activities specifically for cancer immunotherapy.